JUSTIFYING THE OPTIMALITY OF ESTABLISHED REGIMES FOR SWISS CHEESE DOUBLE- SIDED PRESSING - Manukyan Samvel (Academic Scientific Journal of Chemistry, 2020)
. The article discusses conditions when, under the established regime of double-sided pressing, which results in a more equally dimensioned distribution of moisture in Swiss cheese, the prerequisites for microbiological processes flowing are improved, as evidenced by the results of biochemical investigations. A new constructive solution is also proposed for double-sided cheese pressing molds with the possibility of fully automating the processes of molding and pressing, using mechanisms of step pressing of the cheese mass with a reduction in the number of pneumatic cylinders, with the automatic controlling valve of cheese grain filling and cheese removal by a telescopic pneumatic cylinder.